x+3/x^2-3x+3/x^2+3x+2x-18/x^2-9
Thực hiện phép tính, rút gọn
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=x^2+2x-8-x^2-2x-1=-9\)
b: \(=\dfrac{x^2+6x+9+3x-9+2x^2-18x}{x\left(x-3\right)\left(x+3\right)}\)
\(=\dfrac{3x^2-9x}{x\left(x-3\right)\left(x+3\right)}=\dfrac{3x\left(x-3\right)}{x\left(x-3\right)\left(x+3\right)}=\dfrac{3}{x+3}\)
Bài 3:
\(\Leftrightarrow x^3+64-x^3+25x=264\)
hay x=8
\(1,C=6x^2+23x-55-6x^2-23x-21=-76\\ 2,=\left(2x^4-x^2+2x^3-x-6x^2+6-3\right):\left(2x^2-1\right)\\ =\left[\left(2x^2-1\right)\left(x^2+x-6\right)-3\right]:\left(2x^2-1\right)\\ =x^2+x-6\left(dư.-3\right)\\ 3,\Leftrightarrow x^3+64-x^3+25x=264\\ \Leftrightarrow25x=200\Leftrightarrow x=8\)
Bài 1:
a, (\(x\) - 4).(\(x\) + 4) - (5 - \(x\)).(\(x\) + 1)
= \(x^2\) - 16 - 5\(x\) - 5 + \(x^2\) + \(x\)
= (\(x^2\) + \(x^2\)) - (5\(x\) - \(x\)) - (16 + 5)
= 2\(x^2\) - 4\(x\) - 21
b, (3\(x^2\) - 2\(xy\) + 4) + (5\(xy\) - 6\(x^2\) - 7)
= 3\(x^2\) - 2\(xy\) + 4 + 5\(xy\) - 6\(x^2\) - 7
= (3\(x^2\) - 6\(x^2\)) + (5\(xy\) - 2\(xy\)) - (7 - 4)
= - 3\(x^2\) + 3\(xy\) - 3
46:
\(A=\dfrac{2x^2\left(3x^2-2x+1\right)}{2x^2}-\left(3x^2-x-6x+2\right)\)
\(=3x^2-2x+1-3x^2+7x-2=5x-1\)
Khi x=-0,2 thì A=-1-1=-2
45:
a: \(=\dfrac{-5x^6}{3x^2}=-\dfrac{5}{3}x^4\)
c: \(=\dfrac{2x\left(2x^2-\dfrac{3}{2}x+1\right)}{2x}=2x^2-\dfrac{3}{2}x+1\)
\(\dfrac{x+3}{x^2-3x}+\dfrac{3}{x^2+3x}+\dfrac{2x-18}{x^2-9}\\ =\dfrac{x^2+6x+9+3x-9+2x^2-18x}{x\left(x-3\right)\left(x+3\right)}=\dfrac{3x^2-9x}{x\left(x-3\right)\left(x+3\right)}\\ =\dfrac{3x\left(x-3\right)}{x\left(x-3\right)\left(x+3\right)}=\dfrac{3}{x+3}\)
\(=\dfrac{x+3}{x\left(x-3\right)}+\dfrac{3}{x\left(x+3\right)}+\dfrac{2x-18}{\left(x-3\right)\left(x+3\right)}\)
\(=\dfrac{x^2+6x+9+3x-9+4x-36}{x\left(x+3\right)\left(x-3\right)}=\dfrac{x^2+13x-36}{x\left(x+3\right)\left(x-3\right)}\)